Practising writing skills - Editors, Board of. ([S.l.] : Orient Blackswan, 2013)
This is a textbook for undergraduate students studying Compulsory English in the 3rd and 4th semesters at Davangere University, Davangere, Karnataka. The book mainly focuses on important written communication skills essential for further study as well as for success at the workplace. Each chapter has an introduction to the topic and provides examples that students of English can use as models, followed by exercises which give students the opportunity to develop their writing skills and to test their ability.